Gagasan Amandemen Undang-Undang Dasar Tahun 1945 Kelima Sebagai Tindakan Reformasi Hukum - Sumarni Rusdi (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to determine whether or not the fifth Amendment of the 1945 Constitution as the written Constitution of the State of Indonesia which has become a mecca in formulating laws and regulations for more than the last twenty-five years is still able to meet the demands of the dynamics of the current administration or whether radical changes need to be made by changing the main mecca. Along with the current government and a few years ago. The executive and legislative parties even managed to form several legal products that were eventually criticized and rejected by the public. Therefore, it is necessary to limit the power in the field of legislation that must be given to the party whose authority it is. Based on the theory of limiting the President's power, he is the party that executes and implements the law. In Indonesia, the executive is involved in the process of forming legal products. Even the judiciary also acts as a legislator rather than a negative legislator. Efforts to maintain the position of independent commissions and emphasize regional elections so that we do not need to return to the old model. This research will discuss the ideas of change that should be urgent in the current Indonesian constitutional order, and be able to meet the needs of the future. The method used in this writing is Normative law. By conducting approaches to legislation, conceptual, historical approaches, comparisons and using qualitative analysis methods.